Kindergarten teachers’ emotional intelligence and surface acting: the chain mediating effects of self-efficacy and work engagement - Shucun Sun; Zhonglian Yan; Caixia Sun (Frontiers in Psychology)
BackgroundEmotional labor, distinct from physical and mental labor, has gained significant attention in contemporary organizational psychology research. As a strategy for performing emotional labor, surface acting refers to the process of faking emotions to meet the demands of organizations’ norms. This study aimed to investigate the relationship between emotional intelligence and surface acting among Chinese kindergarten teachers, focusing on the mediating role of self-efficacy and work engagement.MethodsIntegrating the conservation of resources theory and the job demands-resources model, a questionnaire survey was conducted among 1,017 Chinese kindergarten teachers using Wong & Law Emotional Intelligence Scale, Self-Efficacy Scale, Utrecht Work Engagement Scale, and Surface Acting Scale. SPSS 26.0 was used to conduct descriptive statistics and correlation tests. Structural equation modeling and mediation analysis were constructed using AMOS 28.0.ResultsThe results showed reveals several key findings. Firstly, kindergarten teachers’ emotional intelligence significantly positively predicted surface acting rather than negatively. Secondly, self-efficacy and work engagement, respectively, mediate the relationship between emotional intelligence and surface acting in kindergarten teachers. Additionally, self-efficacy and work engagement have chain mediating effects in the relationship between kindergarten teachers’ emotional intelligence and surface acting.ConclusionThe research findings reveal the influencing mechanism of kindergarten teachers’ emotional intelligence on surface acting, providing a theoretical basis and practical implications for understanding and promoting the reasonable use of surface acting by kindergarten teachers in the Chinese context.